Integrating Psychological Data for Policy: A Study on the Mental Health of First-Year Students at Universitas Negeri Semarang - Anandita, Nadine Salsabila; Margereta, Elsi; Mahanani, Fatma Kusuma (Universitas Negeri Semarang, 2025)
Mental health is essential for first-year college students, affecting their transition and academic success. The transition phase involves significant challenges due to major life changes. This study presents data on the mental health conditions of first-year students at Universitas Negeri Semarang (UNNES) and emphasizes the need for comprehensive, community-based interventions. A quantitative cross-sectional approach was utilized, surveying 410 first-year students from the 2024 cohort using the Depression Anxiety Stress Scales (DASS-21). Findings revealed high levels of anxiety, followed by depression and stress, with factors such as gender, age, and geographic origin significantly influencing mental health outcomes. Differences in admission pathways and tuition levels also provided valuable context. A comprehensive intervention strategy is proposed to address these issues, combining quarterly and daily components. The quarterly program, Q-CARE (Quarterly – Campus Adaptation & Resilience Enhancement), involves mandatory mental health screenings, personalized counseling referrals, and mentor check-ins. The daily support system includes mood journaling integrated into classroom attendance, motivational posters with QR codes linking to counseling services, and a